Pug blasts off - May, Kyla (May, Kyla. Diary of a pug, 2019)
Baron von Bubbles (Bub) is a pug who wants nothing more than to help his human Bella in her craft projects for school, though he is a little apprehensive about the rocket she is making for the Inventor Challenge--so when he ruins the rocket while trying to get at Nutz the squirrel he needs to find a way to make it up to Bella.